2010
DOI: 10.1592/phco.30.8.812
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Exogenous Albumin Administration for the Prevention of Ifosfamide‐Induced Encephalopathy

Abstract: Prophylactic therapy with exogenous albumin is not an effective strategy for the prevention of IIE. The novel risk-stratification model appears to be an effective method for predicting patients with the greatest potential for developing this adverse effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 12 publications
0
19
1
Order By: Relevance
“…Further, low serum albumin levels are known to be associated with increased risk of severe ifosfamide-induced neurotoxicity [19]. Yet, in one study, prophylactic administration of exogenous albumin did not prevent ifosfamide-induced encephalopathy [20]. Taken together, although our study showed low albumin levels is associated with methotrexate clearance, given the unlikelihood of redistribution and amelioration of encephalopathy, we do not recommend albumin repletion to prevent delayed clearance prior to methotrexate administration.…”
Section: Discussionmentioning
confidence: 52%
“…Further, low serum albumin levels are known to be associated with increased risk of severe ifosfamide-induced neurotoxicity [19]. Yet, in one study, prophylactic administration of exogenous albumin did not prevent ifosfamide-induced encephalopathy [20]. Taken together, although our study showed low albumin levels is associated with methotrexate clearance, given the unlikelihood of redistribution and amelioration of encephalopathy, we do not recommend albumin repletion to prevent delayed clearance prior to methotrexate administration.…”
Section: Discussionmentioning
confidence: 52%
“…The association of age with IRE was addressed in five articles ( Howell, Szabatura, Hatfield Seung, & Nesbit, 2008 ; Kettle et al, 2010 ; Lo, Shen, Chen, Dong, & Wu, 2016 ; Richards et al, 2010 ; Szabatura et al, 2015 ). There was no significant age difference between patients with and without IRE in four of these studies ( Howell et al, 2008 ; Kettle et al, 2010 ; Lo et al, 2016 ; Szabatura et al, 2015 ). Howell and colleagues (2008) completed a retrospective case-control study of 45 sarcoma patients who received ifosfamide, with and without the use of aprepitant.…”
Section: Resultsmentioning
confidence: 99%
“…The authors of all seven studies examined renal insufficiency as a risk factor for IRE. Renal insufficiency, measured by serum creatinine (SCr) in mg/dL and creatinine clearance (CrCl), was reported as a risk factor in four studies ( Kettle et al, 2010 ; Lo et al, 2016 ; Richards et al, 2010 ; Szabatura et al, 2015 ). Kettle and colleagues (2010) reported that patients with IRE had higher mean SCr, 1.05 vs. 0.85, than patients without IRE ( p = .04), although CrCl was not significantly different.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, there are currently no studies exploring the use of single-agent thiamine versus no prophylactic agent for the prevention of IIE. 7,8 In April 2014, the University of North Carolina Medical Center (UNCMC) modified ifosfamide, carboplatin, and etoposide (ICE) chemotherapy regimens (ifosfamide 5 g/m 2 , carboplatin AUC 5, and etoposide 100 mg/m 2 ) to include thiamine 100 mg given intravenously every six hours starting on admission and continuing until discharge. This study aims to compare the incidence of IIE at UNCMC to that of Duke University Hospital (DUH), which does not routinely use prophylaxis for IIE.…”
mentioning
confidence: 99%